Cassava brown streak - Legg, James P.; Kumar, P. Lava; Kanju, E. (CAB International, 2015)
Cassava 'brown streak' disease (CBSD) is an economically important constraint in important cassava-growing areas of East, Central and Southern Africa. In addition to causing a dry necrotic rot in the tuberous roots of infected plants, which can render them inedible, CBSD depresses yields through reducing plant growth. This pandemic of CBSD is driven by the high abundance of the whitefly vector, Bemisia tabaci, coupled with uncontrolled movements of infected cuttings used as planting material. This chapter describes the disease symptoms, distribution, economic impact, aetiology, epidemiology and management strategies of CBSD. The taxonomy, genome organization, diversity, host range, transmission and diagnostic methods of the causal agent are also described. Both host plant resistance and cultural methods are being used to manage the effects of the disease. Recent progress in both field- and laboratory-based experimentation to develop effective control strategies for CBSD means that there are improved prospects for tackling this important constraint to cassava production in future years.